(untitled) (Baghdad Science Journal, 2019)
In this study, the CR-39 detector technique was used, to estimate the uranium concentration from the soil in midland refineries Company (Doura refine (, Baghdad, Iraq. Uranium concentrations in soil samples have been measured using solid state nuclear track detector type CR-39. Nine soil samples were collected from different areas within the Doura refinery and other soil samples were collected form Abu Tayara Street and ALshortaa District outside the refinery for comparison. The results showed variable values for uranium concentrations. The average value of uranium concentration was found to be 0.37 ppm in doura refinery. For areas outside the refinery, the concentration of uranium was 0.008 ppm. These results were less than the global limit.